Enhancing Islamic Economic Literacy through Islamic Education: A Contextual and Evaluation-Based Approach - Reni Marlina; Wiwin Awaliyah; Neni Utami Adiningsih (Indonesian Technology and Education Journal, 2026)
The rapid growth of Islamic financial institutions has not been accompanied by an equivalent increase in Islamic economic literacy, particularly among young learners. This gap reflects a critical issue where individuals possess basic knowledge of Sharia principles but lack the ability to apply them in real financial decision-making. Therefore, this study aims to develop a comprehensive framework for enhancing Islamic economic literacy through Islamic education by integrating contextual and evaluation-based approaches. This study employs a qualitative research design using a systematic literature review. Data were collected from peer-reviewed journal articles, academic books, and official reports indexed in reputable databases such as Scopus and Google Scholar. The inclusion criteria focused on studies related to Islamic economic literacy, contextual learning, and evaluation-based education published within the last ten years. The data were analyzed using thematic analysis to identify key patterns, relationships, and research gaps. The findings indicate that Islamic economic literacy remains largely conceptual and has not been fully internalized into practical financial behavior. The implementation of contextual learning significantly improves learners’ understanding by linking Islamic economic principles to real-life situations. In addition, evaluation-based strategies such as reflective and performance-based assessments play a crucial role in strengthening behavioral transformation and ensuring the sustainability of literacy outcomes. This study contributes by proposing an integrative educational framework that bridges the gap between knowledge and practice through contextual relevance and continuous evaluation. The novelty lies in its multidimensional approach, emphasizing the integration of cognitive, behavioral, and ethical aspects within Islamic economic education.